Progression of radiographic fibrosis in rheumatoid arthritis-associated interstitial lung disease - Chai, Dandan; Sun, Di; Wang, Yuanying; Song, Yawen; Wu, Na; Ye, Qiao (Frontiers in Medicine, 2023)
Background and objectives: Preclinical interstitial lung disease (pILD) may represent the early stages of rheumatoid arthritis-associated interstitial lung disease (RA-ILD).However, the characteristics, clinical outcomes, and risk factors associated with fibrosis progression in RA-ILD, including pILD and ILD, remain poorly understood.Methods: Baseline data were compared between patients with RA-ILD and those with RA alone. Multivariate logistic regression and Cox regression analyses were performed to identify risk factors associated with the prevalence and imaging progression of RA-ILD, respectively.Results: Among the 371 enrolled RA patients, 32.3% had RA-ILD. Multiple logistic regression analyses identified age over 60.0 years (OR 2.22), smoking (OR 2.09), diabetes mellitus (DM) (OR 3.09), mixed connective tissue disease (MCTD) (OR 2.98), serum lactate dehydrogenase (LDH) levels exceeding 250.0 U/L (OR 6.73), and positive anti-cyclic citrullinated peptide (anti-CCP) antibody (OR 2.06) as independent risk factors for RA-ILD (P<0.05 or 0.01). Among the 98 RA-ILD patients who underwent follow-up for a median duration of 19.1 months, 51.0% demonstrated fibrotic progression on high-resolution computed tomography (HRCT).Multiple Cox regression analysis identified DM (HR 2.03), Disease Activity Score in 28 joints-Erythrocyte Sedimentation Rate (DAS28-ESR) greater than 5.1 (HR 2.21), and baseline HRCT scores exceeding 5.0 (HR 2.30) as independent risk factors for fibrosis progression in RA-ILD (P<0.05 or 0.01).Conclusions: Nearly one-third of RA patients in this cohort had prevalent pILD or ILD, and half of them demonstrated imaging progression during follow-up. DM, higher DAS28-ESR, and advanced HRCT scores were identified as independent risk factors for progressive fibrosis in RA-ILD.